Terapia transfusional em pequenos animais - Prado, Gabriela Campoy Pereira do [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Blood transfusion is a very important therapeutic and profilatic procedure. However, the most part of the transfusions in animals in Brazil are done with total blood. The transfusion therapy made in an appropriate way, with hemotherapic products, can save lives and warranties a better health to patients. In all transfusion procedures, the cross match test must be done because there are lots of different blood group types, based on erythrocytes antigen. A slow infusion rate and intensive patient monitoration help to prevent transfusion reactions, mainly hemolytic reactions

A transfusão sanguínea é um procedimento terapêutico e profilático muito importante, porém a maior parte das transfusões em animais no Brasil ainda é feita somente com sangue total. A terapia transfusional realizada de forma adequada, com adequados produtos hemoterápicos, pode salvar vidas e melhorar a saúde dos pacientes. Em todas as transfusões deve-se realizar teste de reação cruzada devido à grande gama de tipos sanguíneos, de acordo com os diferentes antígenos. A lenta taxa de infusão e a monitoração intensiva do paciente auxiliam na prevenção das reações transfusionais, principalmente as reações hemolíticas
Keywords: Sangue - Transfusão; Bancos de sangue; Veterinária de pequenos animais; Dogs; Blood bank